Gut microbiota affects the progression of colorectal cancer under the intervention of exercise - Tao, Linlin; Zhou, Huan; Shao, Wenjiao; Liu, Dongmei; Ruan, Yingwen; Chen, Mingwei (Frontiers in Microbiology, 2026)
Colorectal cancer (CRC) ranks as the third most common cancer globally, accounting for 10% of cases, and is the second leading cause of cancer-related death. Exercise can maintain/restore the body’s internal balance at multiple levels to prevent pathologies, although its mechanism is complex and involves multiple systems. While physical activity improves colon cancer patients’ quality of life and reduces discomfort, how it works remains unclear. To explore this, we constructed a rat CRC model. We performed 16S rRNA and nontargeted metabolomics sequencing and analyzed the results to screen distinct intestinal microbes and their metabolites. To clarify the links among these microbes/metabolites, intestinal barrier function, and inflammatory markers, we used qRT–PCR, immunohistochemistry, and ELISA to verify the effects of exercise intervention on intestinal barrier function and inflammatory factor expression. We also checked the expression of the PCNA gene (a proliferation index) to assess cell proliferation. In vivo, different exercise interventions hindered DMH-induced colon cancer progression in rats and reshaped the gut microbiota. They increase the number of beneficial bacteria, such as Bifidobacterium, and reduce the number of harmful bacteria, such as Escherichia-Shigella. Compared with the Model group, exercise restored intestinal barrier function, promoted anti-inflammatory factor expression, and suppressed proinflammatory factor expression by regulating the gut flora. Overall, exercise intervention curbs CRC development by modulating gut flora–metabolite interactions, restoring the intestinal barrier, and adjusting inflammatory expression. This study confirms the inhibitory effect of exercise on CRC progression. These findings show that different intensities of exercise can impact CRC intestinal barrier function and inflammatory factor levels by balancing the gut flora and metabolites, suggesting a new CRC prevention/treatment approach.